Facilitators of Sense of Belonging Among People With Intellectual and Developmental Disabilities: A Systematic Review. (June 2023) - Gur, Ayelet; Bina, Rena
Background: This review synthesizes the available literature regarding factors which facilitate a sense of belonging in people with intellectual and developmental disabilities, and provide a comprehensive integrative view of the subject.Methods: Four electronic databases were searched, and 13 studies met inclusion criteria for review. The "standard quality assessment criteria for evaluating primary research papers from a variety of fields" indicated satisfactory quality. Factors which facilitate a sense of belonging in people with intellectual and developmental disabilities were analyzed into themes.Results: Sense of belonging is enhanced by feeling respected, accepted, and valued (Subjectivity). These experiences are more likely to be achieved in a familiar and safe environment (Dynamism), and with access to platforms for social interactions (Groundedness), where a sense of relatedness and connectedness achieved by shared experiences with others (Reciprocity). Sense of belonging is associated with committed action of people with disability, taking assertive action or being agentic (Self-determination).Conclusion: Sense of belonging is a unique concept that should be addressed in disability research and practice.